2007
DOI: 10.4161/cbt.6.8.4363
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 interacts with integrin β1 and modulates pancreatic cancer cell growth, survival and invasion

Abstract: Neuropilin-1 (Np-1) is a coreceptor for vascular endothelial growth factor-A (VEGF-A), and both are expressed at high levels in pancreatic ductal adenocarcinomas (PDACs). While VEGF-A has been implicated in tumor angiogenesis, the role of Np-1 in PDAC is less clearly defined. Accordingly, PANC-1 pancreatic cancer cells, which express relatively high levels of Np-1, were transfected with the Np-1 antisense cDNA. By comparison with sham transfected cells, Np-1 antisense expressing clones (Np-1AS) exhibited decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 36 publications
3
99
0
Order By: Relevance
“…The PlexinA1 coreceptor Nrp1 was also originally identified as a surface protein mediating cellular adhesion (Shimizu et al, 2000). Nrp1 was found to interact with β1 integrin in pancreatic carcinoma cells and to be important for integrin‐mediated anchorage‐independent growth and adhesion (Fukasawa et al, 2007). Knockdown of Nrp1 has also been shown to inhibit endothelial cell adhesion to fibronectin by altering the functional activity of α5β1 integrin (Valdembri et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The PlexinA1 coreceptor Nrp1 was also originally identified as a surface protein mediating cellular adhesion (Shimizu et al, 2000). Nrp1 was found to interact with β1 integrin in pancreatic carcinoma cells and to be important for integrin‐mediated anchorage‐independent growth and adhesion (Fukasawa et al, 2007). Knockdown of Nrp1 has also been shown to inhibit endothelial cell adhesion to fibronectin by altering the functional activity of α5β1 integrin (Valdembri et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because Nrp1 modulates the balance between cell proliferation and survival in other cell types (16,17,19,58), we compared indices of proliferation and programmed cell death in the lungs of mice after FA and CS exposure. Overall, there tended to be fewer proliferating cells in the distal lung parenchyma of CCSP-rtTA/tetO-Cre/Nrp1 flox/flox mice than in littermate controls, but these differences were not statistically significant, and the amount of cell proliferation was not altered by chronic smoke exposure in mice of either genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that high levels of Nrp1 may attenuate apoptosis (58). We therefore tested whether conditional Nrp1 deletion altered the balance between CS-induced cell death and proliferation in our model, thereby leading to altered alveolar structure.…”
Section: Effects Of Cs Exposure and Pulmonary Epithelial Nrp1 Deletiomentioning
confidence: 99%
“…20,21 NRP1 is expressed at high levels in several tumor cells, where it has been implicated in cell migration and survival. 11,12,[22][23][24][25][26][27] Recently, our group showed that VEGF189 binds to NRP1, 10 in addition to VEGF165. However, the role of VEGF189-NRP1 association in survival has not been elucidated.…”
Section: Overexpression Of Vegf189 In Breast Cancer Cells Induces Apomentioning
confidence: 99%
“…11,12,14,[22][23][24][25][26] As NRP1 is widely expressed in our derived MDA-MB-231 clones, the effects of VEGF isoforms on survival/apoptosis may involve NRP1. The silencing of NRP1 decreased the apoptosis of clones overexpressing VEGF189 under serum starvation or doxorubicin treatment, and resulted in more necrosis in both conditions than observed for shCtl-transfected V189 clones.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%